Establishment of hypoxia-induced invadopodia model and phenotype characterisation of MDA-MB- 231 breast cancer cell line - Hamad, Hamad Hamad Ali (2019)
Breast cancer is one of the most prevalent cancers diagnosed in women. The majority of mortalities attributed to cancer are due to a critical process in which the cancer cells invade and migrate away from the primary site (i.e. the Breast) to another site such as the brain and bones of which is termed metastasis. One of the mechanisms or tools that tumour cells utilize for the invasion of cancer cells is through the degradation of the extracellular matrix (ECM) by specific actin-foot protrusions characterized as invadopodia. In solid tumours, the invasiveness of cancer cells markedly increases due to hypoxia (low oxygen) that exists in 80% of cancer patients. Previous reports have investigated several mechanisms of invadopodia formation, such as invadopodia components, signalling pathways, and microenvironments. However, limited information is available regarding the utilization of carbon and nitrogen sources in hypoxia-induced MDA-MB-231 cells that may be required for invadopodia formation. Therefore, to achieve the primary objective of this study, a number of methods were employed. First, an invadopodia assay was used to determine the effect of the passage number on invadopodia formation. This was also used to determine the effect of the hypoxia condition on the invadopodia formation treated with 0.5 mM DMOG and incubated in a hypoxia chamber. The second method was the western blot technique. This method was used to investigate the expression of the fundamental proteins of hypoxia, including the hypoxia-inducible factor 1α (HIF-1α) and the vascular endothelial growth factor (VEGF). In addition, to detect the expression of the essential proteins involved in invadopodia formation, including matrix metalloproteinase-2 (MMP-2), the Rho guanine nucleotide exchange factor 7 (-PIX) under hypoxia was also used. The third method, Phenotype microarray for Mammalian cells (PMM), was used to ascertain the essential chemical substrates as a nutrient for MDA-MB-231 cells in forming invadopodia under hypoxia. This powerful tool provides a platform to extensively analyse living cellular phenotypes in response to microenvironment changes or chemical treatments through 96 well plates preloaded with carbon-energy and nitrogen substrates. PMM technology is a new colorimetric assay which is used to measure the redox energy generated when cells oxidise chemical substrates. The results of this study showed that invadopodia formation was significantly affected by the cell line passage number making the cells unable to accomplish gelatin degradation in passage numbers 15 to 35. Therefore, for the following experiments, a low passage number was considered in order to achieve accurate results. The results also revealed that the hypoxia condition using 1% O2 in the hypoxia chamber and 0.5 mM DMOG treatment led to an increase in the number of cells forming invadopodia and induced gelatin degradation. At the molecular level, the western blot analysis proved that HIF-1α in normoxia was degraded while under hypoxia, it dramatically increased. Furthermore, VEGF, MMP-2 and -PIX levels significantly increased in hypoxia compared to normoxia. Here, the proteins played an essential function in invadopodia formation. Finally, the PMM results elucidated that 11 chemical substrates were strongly nourished by MDA-MB-231 cells as a single source for survival under hypoxia condition, such as Dextrin. These substrates could potentially be required for invadopodia formation under a hypoxic condition. Accordingly, these substrates could prove to be potential energy sources for cancer invasion. The findings of this study also propose utilizing certain types of carbon sources such as dextrin as drug carriers in order to enhance the effectiveness of chemotherapy against the hypoxia region and invadopodia formation. As with many research studies, there are certain limitations. However, the author of this study believe that the findings will offer a useful starting point in the cancer invasion field of study, particularly invadopodia formation. Future work could be undertaken to confirm the findings of this study by using a phenotype microarray on other types of highly invasive cells and to confirm the effect of each significant chemical substrate on invadopodia formation.